The Influence of Quality of Work Life (QWL) Performance on Employee Performance Through Organizational Citizenship Behavior (OCB) at Royal Prima Hospital in 2025 - Darnedy Fatwa Mely Santy; Ermi Girsang; Sri Lestari Ramadhani Nasution; Irza Haicha Pratama (Yayasan Mata Pena Madani, 2025)
Voluntary work behavior that goes beyond formal employee responsibilities (OCB) cannot develop optimally without attention to Quality of Work Life (QWL). QWL reflects the organization's efforts in creating a work environment that supports the physical, psychological, and social well-being of employees, which ultimately impacts on improving individual and organizational performance. The formulation of the problem of this research is how does Quality of Work Life (QWL) influence employee performance through Organizational Citizenship Behavior (OCB) at Royal Prima Hospital in 2025? This study uses a quantitative approach. The results of the study There is no significant influence between the variable of tenure and performance at Royal Prima Hospital Medan. There is a significant influence between the variable of Quality of Work Life (QWL) and performance at Royal Prima Hospital Medan. There is a significant influence between the variable of Organizational Citizenship Behavior (OCB) and performance at Royal Prima Hospital Medan. There is a significant influence between the variable of Leadership and performance at Royal Prima Hospital Medan. There is a significant influence between the variable of Satisfaction and performance at Royal Prima Hospital Medan. There is a significant influence between the variable of encouragement and performance at Royal Prima Hospital Medan. The most dominant variable with the greatest influence on performance is motivation because it has an Exp B value of 7.348.